Development of a brain simulator for intracranial targeting: Technical note. (January 2019) - Carolus, A.; Hesse, M.; Rudak, B.; Weihe, S.; Brenke, C.
Highlights: Surgical high challenging subjects as neurosurgery profit from simulator training. A variety of simulators has been developed using physical modality and virtual reality aspects. Modern neurosurgery requires a simulator which incorporates navigated intracranial targeting. A physical model based skull and brain is created and a feedback system is included. Different panels with stell balls represent different neurosurgical target points. The simulator is in an infancy stage but includes some new ideas. Abstract: Learning and enhancing of manual skills in the field of neurosurgery requires an intensive training which can be maintained by using virtual reality (VR)-based or physical model (PM)-based simulators. However, both simulator types are limited to one specific intracranial procedure, e.g. the application of an external ventricular drainage (EVD), and they do not provide any accuracy verification. We present a brain simulator which consists of a 3D human skull model having five electroconductive balls in its interior. The installed balls represent intracranial target points providing various accuracy problems in neuronavigation. They are electrically contacted to lamps getting an optical signal by touching them with a current-carrying target tool. The simulator fulfills two requirements: First, it can prove the accuracy of navigation systems and algorithms. Second, it allows becoming familiar with a navigation system's application in an ex vivo setting. It could be a helpful device in neurosurgical skills labs.